Analisis Pengaruh Kuat Tarik Geosintetik Pada Perkuatan Tanah Lunak Metode Geosynthetic Encased Stone Columns (GESC) - Julita Hayati; Syahidus Syuhada; Celvin Shahroni (Borneo Engineering: Jurnal Teknik Sipil, 2025)
Infrastructure development must consider soil conditions to avoid settlement and bearing capacity failure. This problem can occur if construction is carried out on soft soil due to the nature of soft soil, which has low load-bearing capacity and high compressibility. Soft soil is found in the Indrapura-Kisaran Toll Road Construction Project at STA 112+550 and has a geometry that requires a high embankment, necessitating soil reinforcement to address the issue. In this study, the Geosynthetic Encased Stone Columns (GESC) method was used with variations in geosynthetic tensile strength of 150 kN/m, 200 kN/m, 300 kN/m, and 400 kN/m. The analysis process conducted in this study involves analyzing the bearing capacity and settlement conditions without and with reinforcement using analytical and numerical methods. Generally, the magnitude of bearing capacity and reduction in settlement due to reinforcement with geosynthetic-encased stone columns is influenced by the tensile strength of the geosynthetic, spacing, and installation pattern. After reinforcement, the soil-bearing capacity increased by 75 to 84%. In addition, due to the GESC reinforcement, there was a reduction in settlement of up to 86% using the analytical method and 61.8% using the numerical method. There was an increase in the stability of the embankment, where before reinforcement the stability was 1,453, and after reinforcement, it became 1,596 to 1,828.